2017
DOI: 10.5205/1981-8963-v11i12a22786p5275-5281-2017
|View full text |Cite
|
Sign up to set email alerts
|

Ambiente de pediatria: aspectos que auxiliam no processo de trabalho e na produção de saúde

Abstract: Objective: to identify aspects of the pediatric environment helping the work process and health production. Method: this is a qualitative, exploratory and descriptive study, carried out in the pediatric units of two University Hospitals. The participants were professionals and managers of nursing, totaling 44 participants. Data collection was performed through semi-structured interviews, organized and handled by Nvivo 10 software. Results: data analysis revealed the following categories: << Organization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
2
Order By: Relevance
“…A doença é um ataque à criança como um todo, afetando sua integridade e comprometendo seu desenvolvimento emocional. Os profissionais que atuam na pediatria, em especial os pediatras, devem estar preparados para atender as necessidades dos pacientes e de suas famílias, que no caso da pediatria envolve uma grande expectativa por se tratar de pessoas que estão apenas no início de suas vidas e são, mesmo sadias, dependentes de cuidados (Ribeiro et al, 2017).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A doença é um ataque à criança como um todo, afetando sua integridade e comprometendo seu desenvolvimento emocional. Os profissionais que atuam na pediatria, em especial os pediatras, devem estar preparados para atender as necessidades dos pacientes e de suas famílias, que no caso da pediatria envolve uma grande expectativa por se tratar de pessoas que estão apenas no início de suas vidas e são, mesmo sadias, dependentes de cuidados (Ribeiro et al, 2017).…”
Section: Resultsunclassified
“…Desse modo, pelas características de sua profissão, o pediatra pode ser considerado um profissional predisposto ao desenvolvimento de estresse. Assim, da mesma forma que a sociedade exige e necessita de pediatras competentes e comprometidos, esses profissionais precisam, também, ser acompanhados e melhor avaliados no que tange às suas condições de saúde, principalmente em relação aos aspectos psicossomáticos, nos quais a variável estresse tem um enorme poder de destruição da capacidade de trabalho dos indivíduos (Ribeiro et al, 2017).…”
Section: Resultsunclassified
“…The pediatric hospital environment should consider and respect the cultural values, the autonomy, the privacy, the individuality and the ways of life of whom is cared, prioritizing the physical and psychical well-being and its family, beyond of being welcoming, harmonic and humanized. 22 In this way, the deponents emphasized the comfort, the privacy and the humanization, as particularities of a welcoming environment that make it possible the child to experience its death worthily.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect may be related to the pediatric environment. A study carried out with nursing professionals at a university hospital in southern Brazil showed that professionals working in this sector have a greater chance of developing and increasing strategies to improve care to children and their families (13) .…”
Section: Repercussions Of Educational Actions (Year 2016 and 2017)mentioning
confidence: 99%